Liquid Crystals and Phase Equilibria Binary Bile Salt-Water Systems - Marques, Eduardo F. (2000)
The phase behavior of several binary sodium bile salt-water systems is investigated over the entire concentration range, with emphasis on concentrated regions beyond the isotropic solution phase. The studied bile acid salts comprise the free salt sodium deoxycholate (SDC), the taurine conjugates sodium taurocholate (STC), sodium taurodeoxycholate (STDC), and sodium taurochenodeoxycholate (STCDC) and the glycine conjugate sodium glycodeoxycholate (SGDC). A combination of classical techniques is used, including phase diagram determination, polarizing microscopy, 2H NMR, and small-angle X-ray scattering (SAXS). The aggregation behavior in the isotropic micellar solutions of STC and STDC is also investigated by pulsed-field gradient NMR self-diffusion. The optical textures and the data from SAXS and 2H NMR clearly point to the formation of hexagonal liquid crystals, possibly of the reverse type, beyond the micellar solution for all the bile salts. Several unusual kinetic effects, such as very slow equilibration times and the formation of transient spherulitic crystals in biphasic regions, are observed. The phase diagrams and structural data are qualitatively discussed in terms of the molecular structure and solubility of the different salts. The formation of lyotropic liquid crystals by bile salts, which has remained unknown for decades, is clearly demonstrated in this work.